Structure and Antiparasitic Activity Relationship of Alkylphosphocholine Analogues against Leishmania donovani - Humera Ahmed; Katharine C. Carter; Roderick A.M. Williams (Microorganisms, 2020)
Miltefosine (Milt) is the only oral treatment for visceral leishmaniasis (VL) but its use is associated with adverse effects, e.g., teratogenicity, vomiting, diarrhoea. Understanding how its chemical structure induces cytotoxicity, whilst not compromising its anti-parasitic efficacy, could identify more effective compounds. Therefore, we systemically modified the compound’s head, tail and linker tested the in vitro activity of three alkylphosphocholines (APC) series against Leishmania donovani strains with different sensitivities to antimony. The analogue, APC12, with an alkyl carbon chain of 12 atoms, was also tested for anti-leishmanial in vivo activity in a murine VL model. All APCs produced had anti-leishmanial activity in the micromolar range (IC50 and IC90, 0.46– > 82.21 µM and 4.14–739.89 µM; 0.01– > 8.02 µM and 0.09–72.18 µM, respectively, against promastigotes and intracellular amastigotes). The analogue, APC12 was the most active, was 4–10 fold more effective than the parent Milt molecule (APC16), irrespective of the strain’s sensitivity to antimony. Intravenous administration of 40 mg/kg APC12 to L. donovani infected BALB/c mice reduced liver and spleen parasite burdens by 60 ± 11% and 60 ± 19%, respectively, while oral administration reduced parasite load in the bone marrow by 54 ± 34%. These studies confirm that it is possible to alter the Milt structure and produce more active anti-leishmanial compounds.